International business and the eclectic paradigm: developing the OLI framework - Mudambi, Ram (Journal of International Business Studies, 2004)
For more than two decades, the eclectic OLI paradigm developed by John Dunning has provided a unifying framework for research on multinational enterprises. Numerous scholars, including John Dunning himself, have continuously extended it to analyze new research questions emerging with new forms of international business and with increased globalization.